A CP-ABE Algorithm Based HDFS Distributed Storage Data Security Solution. Issue 7 (March 2020) - Li, Nengneng; Wang, Yingcun; Xu, Xiwei; Liu, Xiaoyang
Abstract: With the continuous development of technology, traditional data encryption technology has been cracked, existing data security measures can no longer meet the user's data security needs, and the problem of data security remains the primary issue facing cloud storage. Based on the analysis of cloud storage data security, this paper proposes a CP-ABE-based HDFS distributed storage data security solution to the problems of traditional attribute-based data encryption technology (CP-ABE). After analysis of the algorithm, the algorithm can ensure the security of the data stored on the cloud platform users through the attribute-based encryption algorithm.